Applying big data and stream processing to the real estate domain. Issue 9 (2nd September 2019) - García-González, Herminio; Fernández-Álvarez, Daniel; Labra-Gayo, José Emilio; Ordóñez de Pablos, Patricia
ABSTRACT: In this paper, we propose an architecture that combines Big Data and Stream Processing which can be applied to the Real Estate Domain. Our approach consists of a specialisation of Lambda architecture and it is inspired by some aspects of Kappa architecture. As a proof of this solution, we show a prototype developed following it and a comparison of the three architecture quality models. Finally, we highlight the differences between the proposed architecture and similar ones and draw some future lines following the present approach.